Mechanical properties and durability of self compacting concrete containing supplementary cementitious materials / Aiad Hamed Hassan - Aiad, Hamed Hassan (2014)
Self-compacting concrete (SCC) is a fluid mixture which is suitable for placing in structures with congested reinforcement without vibration. Self-compacting concrete development must ensure a good balance between deformability and compactability. The latter is affected by the characteristics of materials and the mix stability proportions and it becomes necessary to evolve a procedure for the mix design of SCC. In this research, the engineering and durability performance of a grade 40 self-compacting concrete containing supplementary cementitious materials (SCM) as cement replacement were studied. Twenty seven trial mixes were conducted and four different mixes were then chosen for further investigation. They are SCC containing ordinary Portland cement (OPC), fly ash (FA), rice husk ash (RHA) and ground granulated blast-furnace slag (GGBS). Three different quantities of cement were used i.e. 440, 432, and 406 kg/m3. For FA, RHA and GGBS, three different cement replacement levels were used i.e. 5%, 10% and 15%. Different fresh concrete tests were conducted. Slump flow spread and V-funnel tests were used to determine the filling ability. L-box and J-ring tests were used to determine passing ability and segregation resistance. The results for fresh concrete showed that flowability of concrete increased with increasing binder materials and dosage of superplasticizer. Mechanical properties of self-compacting concrete such as compressive strength, flexural, splitting tensile, elastic modulus and drying shrinkage were investigated. Testing for compressive strength samples was conducted at 7 to 660 days; flexural tensile, splitting tensile strengths and elastic modulus were tested at 28 and 180 days. Drying shrinkage was tested at ages of 7 to 360 days under two types of curing regimes, namely, air drying and water curing. The performance criterion for passing ability was fulfilled for all SCM mixes concrete which contain FA, RHA and GGBS which were suitable for the segregation resistance requirement. The performance of mixture with FA, RHA and GGBS was better compared to those containing control mix (OPC). SCC containing 15% FA was the most effective to provide good filling ability and passing ability compared to mixtures containing RHA (10%) and GGBS (5%). Test results of hardened concretes also revealed that the compressive, splitting tensile and flexural strengths, static and dynamic modulus of elasticity, as well as ultrasonic pulse velocity increased whereas the water absorption and porosity decreased with lower W/B ratio and higher SCM content at 15%, 10% and 5% replacement of OPC by weight. It was also shown that the relative strength of concrete containing SCM such as FA, RHA and GGBS immersed in sulphate solution increased with time compared to air dried specimens. In the drying shrinkage test for all mixes containing FA, RHA and GGBS, the reduction in weight is attributed to the formation of gypsum on the concrete surface which also results in the softening and spalling of the concrete surface. Consequently, experiments revealed that resistance chloride is reduced with increase of compressive strength of concrete containing various SCM particularly with FA and RHA compared to the control OPC mix. The results for the hardened concrete containing SCM showed better strength at 2 years curing age. It yielded favourable outcome in drying shrinkage. Mixes subjected to magnesium sulphate solution showed better compressive strength compared to air dried mixes. In both comparison groups, mixes containing SCM yielded better outcomes compared to control mix. The permeability of SCC containing FA, RHA and GGBS was lower than that of control SCC concrete, thereby improving the durability properties and lowering the porosity of the concrete.